Charity in Islam and Judaism: A Comparative Study of Zakāt and Tzedakah - Qadri, Ahmed Waheed (Al-Irfan, 2025)
Islam and Judaism give a high status to charity because it is a social and religious obligation. If we go throw scriptures, ancient commentaries, and rabbinic traditions, this article gives the comparison of the holy activates of Tzedakah in Judaism and Zakāt(Alam due) in Islam. It explores their social, legal frameworks, roles and theological Study throw a textual comparative methodology. Although the results highlight differences in canvas, implementation, and conceptual enclosing, they also tell us about the great equivalents, such as their heavenly command, mandatory charm, and focus on helping the oppressed. While Tzedakah enforce justice and collective responsibility defined by moral commands, Zakāt works as a system which is a legally connecting system of wealth transmission. At end this study shows conclusion that both systems offer huge basics for social justice, poverty decrease, and interfaith dialog, providing deep evidence to modern values. According to the study's results, both models offer sustainable outlines for social justice, poverty decrease, and interfaith dialog, also providing modern countries important understandings into moral economics and Religion-based methods to welfare.